Determination of pesticide residues in urine by chromatography-mass spectrometry: methods and applications - Birolli, Willian Garcia; Lanças, Fernando Mauro; dos Santos Neto, Álvaro José; Silveira, Henrique C. S. (Frontiers in Public Health, 2024)
Introduction: Pollution has emerged as a significant threat to humanity, necessitating a thorough evaluation of its impacts. As a result, various methods for human biomonitoring have been proposed as vital tools for assessing, managing, and mitigating exposure risks. Among these methods, urine stands out as the most commonly analyzed biological sample and the primary matrix for biomonitoring studies.Objectives: This review concentrates on exploring the literature concerning residual pesticide determination in urine, utilizing liquid and gas chromatography coupled with mass spectrometry, and its practical applications.The examination focused on methods developed since 2010. Additionally, applications reported between 2015 and 2022 were thoroughly reviewed, utilizing Web of Science as a primary resource.Synthesis: Recent advancements in chromatography-mass spectrometry technology have facilitated the development of multi-residue methods capable of simultaneously detecting numerous pesticide residues from various chemical and use classes. Furthermore, these methods encompass analytes from a variety of environmental contaminants, offering a comprehensive approach to biomonitoring. These methodologies have been employed across diverse perspectives, including toxicological studies, assessing pesticide exposure in the general population, occupational exposure among farmers, pest control workers, horticulturists, and florists, as well as investigating consequences during pregnancy and childhood, neurodevelopmental impacts, and reproductive disorders.Future directions: Such strategies were essential in examining the health risks associated with exposure to complex mixtures, including pesticides and other relevant compounds, thereby painting a broader and more accurate picture of human exposure.Moreover, the implementation of integrated strategies involving international research initiatives and biomonitoring programs is crucial to optimize resource utilization, enhancing efficiency in health risk assessment.